Microwave-Assisted Hydroxylation of Benzene to Phenol Over V(V)/MCM-41 Catalysts at Room Temperature - Liu, Tong; Fan, Sujuan; Hou, Jinhui (Asian Journal of Chemistry, 2015)
Direct hydroxylation of benzene to phenol with hydrogen peroxide over catalysts prepared by the metal species e.g., V(V), Cu(II), Co(II) impregnated on MCM-41 was examined at room temperature under microwave irradiation. This paper investigated the catalytic performances of MCM-41 supports prepared by various calcined temperature and time. The results manifested that the V(V)/MCM-41 catalyst gave the highest activity than Cu(II), Co(II)/MCM-41 at same experimental conditions. The influence of various reaction parameters, such as reaction time, amount of catalyst and hydrogen peroxide, on the conversion of benzene was investigated under microwave irradiation. Coupled conventionally heated method gives phenol yield of 5.8 %, the V(V)/MCM-41 gives higher phenol yield of 18.7 % and selectivity of 100 % under microwave irradiation.